OPTIMIZING PANCASILA LEARNING IN CLASS V WITH THE LITERATURE CIRCLE MODEL ON LIFE NORMS MATERIAL - Yuniartining Tiyas; Samsul Wadi; Donna Boedi Maritasari; Hurun In (PIONIR: JURNAL PENDIDIKAN, 2025)
This research aims to improve the learning outcomes of fifth grade students in the Pancasila Education subject, especially regarding norms in life, by implementing the Literature Circle learning model. This model is designed to encourage active student participation through group discussions with specific roles. The research was conducted in two cycles involving 31 students at SD Negeri 3 Sekarteja, using observation sheets and learning outcomes tests as data collection tools, which were analyzed using interpretation. The results of the research showed that there was a significant increase in student learning outcomes, where in the first cycle the majority of students got a score between 70 and 80 with 16% achieving a score of 100, while in the second cycle the number of students who achieved a perfect score increased to 29%, and all students got score above 80. Student participation in discussions also increased, with students who were previously passive becoming more active in asking critical questions and relating the material to personal experiences. Overall, the application of the Literature Circle model is effective in improving learning outcomes and student engagement, so that this model can be used as a suitable learning alternative for Pancasila Education, especially for material that requires in-depth understanding.Keywords: Optimization, Classroom Action Research, Learning Outcomes, Literature Circle